Solid Waste Management and its Problem in Asmara City of Eritrea - Hoda, Md Minhajul; Khan , Masihulla (Journal for Geography, 2025)
Urbanization, rising incomes, and lifestyle changes are major drivers of municipal solid waste generation, especially in developing countries. Asmara, Eritrea, faces significant waste management challenges, particularly due to a large, disorganized open dumping site at Betghiorghish. This site lacks a proper recycling strategy and threatens local biodiversity. A study was conducted to evaluate the types and amounts of waste generated in Asmara, using primary data collected from various economic groups through questionnaires. Study found a positive correlation between urbanization and waste generation. Moreover, different economic strata have different amount and nature of waste. There is report of increasing amount of non-biodegradable waste among the higher income people/region. An integrated sustainable planning is needed to manage the municipal waste.